Responses of Methanogenic and Methanotrophic Communities to Elevated Atmospheric CO2 and Temperature in a Paddy Field - Liu, Yuan; Liu, Xiaoyu; Cheng, Kun; Li, Lianqing; Zhang, Xuhui; Zheng, Jufeng; Zheng, Jinwei; Pan, Genxing (Frontiers in Microbiology, 2016)
Although climate change is predicted to affect methane (CH4) emissions in paddy soil, the dynamics of methanogens and methanotrophs in paddy fields under climate change have not yet been fully investigated. To address this issue, a multifactor climate change experiment was conducted in a Chinese paddy field using the following experimental treatments: (1) enrichment of atmospheric CO2 concentrations (500 ppm, CE), (2) canopy air warming (2°C above the ambient, WA), (3) combined CO2 enrichment and warming (CW), and (4) ambient conditions (CK). We analyzed the abundance of methanogens and methanotrophs, community structures, CH4 production and oxidation potentials, in situ CH4 emissions using real-time PCR, T-RFLP and clone library techniques, as well as biochemical assays. Compared to the control under CE and CW treatments, CH4 production potential, methanogenic gene abundance and soil microbial biomass carbon (SMBC) significantly increased; the methanogenic community however remained stable. The canopy air warming treatment only had an effect on CH4 oxidation potential at the ripening stage. Phylogenic analysis indicated that methanogens in the rhizosphere were dominated by Methanosarcina, Methanocellales, Methanobacteriales and Methanomicrobiales, while methanotrophic sequences were classified as Methylococcus, Methylocaldum, Methylomonas, Methylosarcina (Type I) and Methylocystis (Type II). However, the relative abundance of Methylococcus (Type I) decreased under CE and CW treatments and the relative abundance of Methylocystis (Type II) increased. The in situ CH4 fluxes indicated similar seasonal patterns between treatments; both CE and CW increased CH4 emissions. In conclusion results suggest that methanogens and methanotrophs respond differently to elevated atmospheric CO2 concentrations and warming, thus adding insights into the effects of simulated global climate change on CH4 emissions in paddy fields.